Rotating Magnetic Field-Assisted Reactor Enhances Mechanisms of Phage Adsorption on Bacterial Cell Surface - Bartłomiej Grygorcewicz; Rafał Rakoczy; Marta Roszak; Maciej Konopacki; Marian Kordas; Agnieszka Piegat; Natalia Serwin; Elżbieta Cecerska-Heryć; Miroslawa El Fray; Barbara Dołęgowska (Current Issues in Molecular Biology, 2022)
Growing interest in bacteriophage research and use, especially as an alternative treatment option for multidrug-resistant bacterial infection, requires rapid development of production methods and strengthening of bacteriophage activities. Bacteriophage adsorption to host cells initiates the process of infection. The rotating magnetic field (RMF) is a promising biotechnological method for process intensification, especially for the intensification of micromixing and mass transfer. This study evaluates the use of RMF to enhance the infection process by influencing bacteriophage adsorption rate. The RMF exposition decreased the t50 and t75 of bacteriophages T4 on Escherichia coli cells and vb_SauM_A phages on Staphylococcus aureus cells. The T4 phage adsorption rate increased from 3.13 × 10−9 mL × min−1 to 1.64 × 10−8 mL × min−1. The adsorption rate of vb_SauM_A phages exposed to RMF increased from 4.94 × 10−9 mL × min−1 to 7.34 × 10−9 mL × min−1. Additionally, the phage T4 zeta potential changed under RMF from −11.1 ± 0.49 mV to −7.66 ± 0.29 for unexposed and RMF-exposed bacteriophages, respectively.